An evolutionary perspective on the endogenous instability of capitalist dynamics - Lyubov Klapkiv; Faruk Ülgen (Central European Economic Journal (CEEJ), 2022)
This article is a theoretical and conceptual exploration into the study of the dynamics of financial innovations and their consequences in market economies. Drawing upon the works of Schumpeter and Minsky in an institutionalist and evolutionary tradition, the article puts forward the monetary and financial features of the 21st century economies and the recurrent systemic financial instabilities generated within the context of the financialization process. It then calls for alternative regulatory reforms capable of leading to sustainable economic development. The originality of the analysis lies in the fact that the micro-dynamics of innovations may result in both creative and destructive outcomes since there are some crucial differences between entrepreneurial innovations à la Schumpeter as the positive force in economic development, and financial innovations à la Minsky as the source of instabilities. The article then focuses on the weaknesses and inconsistencies of loosely regulated financial markets and suggests a few principles for relevant financial regulation in an endogenously unstable economy. The main contribution of the article is that financial stability must be regarded as a public good to be provided by an economy-wide regulatory framework under the supervision of a visible public hand. The study of the conditions of financial stability proves to be a matter of a specific social dilemma-opposition between private and public interests-that concerns the organisation and management of financial markets at the macroeconomic level. Such a dilemma leads to the ultimate regulatory issue of spurring the innovation dynamics of financial markets while ensuring systemic stability and sustainability through an appropriate regulatory and supervisory environment.
Keywords: B52; G01; H41; 330; financial regulation; financial crisis; innovation; institutionalist; evolutionary approaches